Preparation & characterization of microcrystalline cellulose from agriculture waste - Nur Aiman, Senusi; Norshahidatul Akhmar, Mohd Shohaimi; Zamani, A. H.; Nurasmat, Mohd Shukri; Mohammad Khairul Azhar, Abdul Razab; Mazlan, Mohamed; Mohamad Asyraf, Mohd Amin; Wan Nur Aini, Wan Mokhtar; Abrar, Ismardi; An'Amt, Bin Mohamed Noor; Nor Hakimin, Abdullah (IOP Publishing Ltd., 2020)
In this work, microcrystalline cellulose was prepared from oil palm trunk by water treated fibre process and alkali bleaching. The prepared samples were characterized by using Fourier-transform infrared spectroscopy attenuated total reflectance (FTIR-ATR), Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD). FTIR-ATR spectra analysis indicates the presence of the hydroxyl group, alcohol, alkane/alkene and imine group. XRD patterns revealed the amorphous nature of the samples and the crystallinity index for extracted cellulose is 48.7 %. SEM images showed the fibrous structure of the microcrystalline cellulose with a size of 50 μm. This research proved that the synthesized microcrystalline cellulose could be potentially used as reinforcement in bio composite for better performance and ductility.